Biogeography and taxonomy of New Zealand Cladocera (Anomopoda, Chydoridae): a review - Kattel, Giri; Augustinus, Paul (2010)
Studies of the biogeography of Cladocera in New Zealand lakes are rare and only a few species of littoral chydorid Cladocera have been documented. Consequently, a number of issues relating to their taxonomy and systematics have yet to be resolved. The majority of chydorid Cladocera in the northern hemisphere have been given new names after a detailed investigation of their morphology and genetic variability. However, knowledge of their inter-hemispheric distribution is poor. It is likely that many species of chydorid Cladocera in the southern hemisphere, including in the New Zealand lakes, will show significant genetic variability from their northern hemisphere counterparts, although this has not yet been investigated. Here we review the taxonomy and biogeography of the New Zealand chydorid Cladocera. This is important when we consider the limited knowledge of New Zealand cladocerans and the consequent difficulties encountered by freshwater ecologists and paleolimnologists when using them to identify rapid environmental changes in the southern hemisphere.